2010
DOI: 10.1123/ijsc.3.2.240
|View full text |Cite
|
Sign up to set email alerts
|

International Sports Commentary Frame and Entertainment: A Cross-Cultural Analysis of Commentary Differences in World Series Broadcasts

Abstract: Numerous studies examining the portrayals of gender, race, and nationality in sports commentary have been conducted through the years; however, comparative analyses of commentaries from different countries have been rare. This study examined commentary from 3 different countries (the U.S., Chinese Taipei, and South Korea) during a Major League Baseball (MLB) World Series. An entertainment theory schema was adopted and the 3 countries were categorized based on dispositional relativity (affiliation) with MLB. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Slovenian sportscasters devote a substantial amount of their on-air dialogue to evaluative commentary. The 44% share of interpretive dialogue found in this research exceeds the amount of interpretation found in previous studies conducted on team sports in Asian and North American cultures (Bryant et al, 1977; Woo et al, 2010). The topics discussed by the announcers depend on the gender and the nationality of the athletes.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Slovenian sportscasters devote a substantial amount of their on-air dialogue to evaluative commentary. The 44% share of interpretive dialogue found in this research exceeds the amount of interpretation found in previous studies conducted on team sports in Asian and North American cultures (Bryant et al, 1977; Woo et al, 2010). The topics discussed by the announcers depend on the gender and the nationality of the athletes.…”
Section: Discussioncontrasting
confidence: 76%
“…In the overall composition of the comments, factual and background descriptors represented 53% of the total commentary. This is less than the share recorded in team sports telecasts in other cultures, which ranged between 59 and 73% Woo et al, 2010). Evaluative commentary comprised 44% of the Slovenian commentary.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Of those, many have focussed on sport media coverage. For instance, Woo et al (2010) conducted a study to examine three countries' television broadcast commentaries of the Major League Baseball World Series. The study found that different frames were used to describe the same visual image.…”
Section: Tbp In Sporting Eventsmentioning
confidence: 99%